Simulating the diffraction grating reflectivity using effective medium theory - Goloborodko, A.A.; Goloborodko, N.S.; Oberemok, Ye.A.; Savenkov, S.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
The features of optical radiation interaction with surface of gratings are
investigated. The diffraction grating is proposed to be used in the effective medium
model to test nanostructured surfaces. This object allows obtaining simultaneous
visualization of different spatial frequencies and estimation of both structure and surface
features of 3D-objects. It was shown that the effective medium model could be used to
predict the reflectivity of nanostructured surfaces by using diffraction gratings with
different depths of profile. Computer simulations show that the filling factor of
composite systems could be an angle dependent function. So, the correct solution of the
inverse problem of finding surface characteristics, such as refraction indices and
absorption coefficients, is related with the angle dependence of filling factor.